Traumatic rupture of a gastrointestinal stromal tumour with intraperitoneal bleeding and haematoma formation. (10th August 2010) - Mohamed, Ahmed; Griffiths, Ewen A; Witkowski, Marek; Witkowska, Katarzyna; Ball, Chris S
Abstract : A 40-year-old man presented with acute abdominal pain and falling haemoglobin after a history of minor abdominal trauma. Radiological imaging showed a large soft tissue mass situated between the anterior stomach wall and peritoneum. At diagnostic laparoscopy, intra-abdominal blood and an encapsulated haematoma were found. The procedure was converted to midline laparotomy and the mass was excised, including a stalk of tissue that connected the mass to the anterior prepyloric stomach wall. The patient recovered well and was discharged after 9 days. Histology confirmed a gastrointestinal stromal tumour surrounded by haematoma formation.